Self-cleaning aquacultural water quality monitoring system design. Issue 17 (2018) - Yueting, Wang; Jiaming, Li; Long, Yu; Xiaoming, Long; Weiqi, Li
Abstract: This paper has designed a system that uses the ultrasonic technology to wash the water quality sensor automatically. The hardware platform of the cleaning system is composed of a processing module, a sensor module, a sampling module and a cleaning module. The proposed system uses the water-pump to convey the aquaculture water to the designed detected-tank via the pipeline and detect the water quality. The water quality sensor installed in the detected-tank is cleaned regularly under the effect of ultrasonic vibration on the bottom plate of the tank. The experimental results demonstrate that in the aquaculture environment, the dissolved oxygen sensor is prone to accumulation of pollutants after 14 hours, the detection value is shifted, and the change is slow. Under the action of ultrasonic cleaning, dissolved oxygen sensor detection spends about 10 min to correct again.